"TERSEMBUNYI", TAPI MENARIK - Eko Prastiyanto; Marianus Subandowo; Retno Danu Rusmawati (Jurnal Education and Development, 2020)
Student interest in English subjects, especially in class VII is still very low. This is caused by various factors, one of which is interest in teaching materials. This study aims to develop teaching materials by utilizing QR code technology as a link between printed books and digital multimedia by means of digital multimedia learning materials in the form of "hiding" in the form of QR codes then students can open them using smartphones. This development research approach model adapts the development procedure developed by Walter Dick and Lou Carey. The results of this study are 1). 89% of students stated that subject teachers used appropriate teaching materials, 2). 91% of students stated that subject teachers used appropriate learning media, 3). 88% of students stated that QR code technology integrated into teaching materials was very interesting and motivating to learn, 4). 88% of students stated that QR code technology that was integrated into teaching materials was well suited to the needs and learning styles of students, 5). 86% of students stated that they were enthusiastic about using QR code technology in learning activities, 6). 88% of students state that QR code technology makes it easy for them to learn independently, 7). 90% of students state that QR code technology facilitates interaction between teachers and them